2012
DOI: 10.1016/j.pubrev.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Colleges’ and universities’ use of Twitter: A content analysis

Abstract: This study explored how colleges and universities are employing Twitter, a popular microblogging tool. Using Kent and Taylor's principles of dialogic communication, a content analysis was performed on individual tweets (n=1130) from 113 colleges and universities. Tweets were coded for whether or not they met each principle of dialogical communication and why. It was found that institutions are not employing Twitter in a dialogic way and they are, instead, employing it primarily as an institutional news feed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 4 publications
3
62
0
5
Order By: Relevance
“…The number of tweets retrieved in past research has been highly variable ranging from a few thousands to millions (Fried et al, 2014;Linvill, McGee, & Hicks, 2012) and in the absence of a consensus on sample size we retrieved $16,000 tweets for each of the four eating occasions, a number that was 10-100 times greater than typical sample sizes in sensory and consumer research. Because the Twitter server has limits on the number of tweets that can be retrieved in each search (Gentry, 2014), multiple searches were performed (Table 1).…”
Section: Retrieval Of Twitter Datamentioning
confidence: 99%
“…The number of tweets retrieved in past research has been highly variable ranging from a few thousands to millions (Fried et al, 2014;Linvill, McGee, & Hicks, 2012) and in the absence of a consensus on sample size we retrieved $16,000 tweets for each of the four eating occasions, a number that was 10-100 times greater than typical sample sizes in sensory and consumer research. Because the Twitter server has limits on the number of tweets that can be retrieved in each search (Gentry, 2014), multiple searches were performed (Table 1).…”
Section: Retrieval Of Twitter Datamentioning
confidence: 99%
“…En ese marco, las herramientas sociales de Internet -blogs, redes sociales, wikis, etc.-aportan al desarrollo del comercio electrónico orientándose hacia el comercio social, en la medida que consideran al usuario, la interacción con la comunidad y la transacción (Huang y Benyoucef 2013;Bai, Yao y Dou, 2015). De este modo, permiten que se genere una comunicación efectiva entre dichas comunidades; a través de estas conversaciones online, se promueve la personalización de productos y servicios para el cliente y su comunidad (Boyd y Ellison, 2007;Alloway y Alloway, 2012;Linvill, McGee y Hicks, 2012). Según Hajli y Sims (2015), el s-commerce se desarrolló por la creciente popularidad de las redes sociales y su integración en plataformas de e-commerce.…”
Section: Comercio Social O S-commerceunclassified
“…McAllister (2012) concluded, "The voices of key stakeholders are being silenced via a media that is intended to provide open forums for dialogue" (p. 319). Similarly, a Twitter study found colleges and universities were not using Twitter to engage in dialogic communication (Linvill, McGee, & Hicks, 2012).…”
Section: Dialogue and Engagementmentioning
confidence: 99%